Comparison of four high-throughput, automated immunoassays for the detection of SARS-CoV-2 antibodies. (September 2021) - Oakey, Jane; Haslam, Shonagh; Brown, Andrew; Eglin, Janet; Houghton, Brittany; Singleton, Dawn
Background: A number of immunoassays have been developed to measure antibodies specific to SARS-CoV-2. More data is required on their comparability, particularly among those with milder infections and in the general practice population. The aim of this study was to compare four high-throughput automated anti-SARS-CoV-2 assays using samples collected from hospitalized patients and healthcare workers with confirmed SARS-CoV-2 infection. In addition, we collected general practice samples to compare antibody results and determine seroprevalence. Methods: Samples were collected from 57 hospitalized patients and nine healthcare workers at 14 days and at 28 days following confirmed SARS-CoV-2 infection. Samples were also collected from 225 patients presenting to general practice. Four assays were used: Abbott Architect IgG, Beckman Coulter DxI 800 IgG, Roche Cobas e801 total antibody and Siemens Advia Centaur XPT total antibody. Results: All four assays showed concordance at 14 days in 83.9% of hospitalized patients and in 66.7% of healthcare workers. All four assays showed concordance at 28 days in 88.4% of hospitalized patients and 77.8% of healthcare workers. The sensitivity to detect recent infection was higher for the IgG assays than the total assays. All four assays showed concordance of 95.1% in the general practice population. Seroprevalence ranged from 4.9 to 5.8% depending on the assay used. Conclusions: All four assays showed excellent comparability, but it may be possible to obtain a negative result for any of the anti-SARS-CoV-2 assays in patients with confirmed previous SARS-CoV-2 infection. An equivocal range would be useful for all anti-SARS-CoV-2 assays.